Exploring adolescents' views of the impact of computer-mediated communication (CMC) on their lives - Verrijdt, Andrew (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MEdPsych (Educational Psychology))--University of Stellenbosch, 2009.